A Neuroprotective Locus Modulates Ischemic Stroke Infarction Independent of Collateral Vessel Anatomy - Lee, Han Kyu; Wetzel-Strong, Sarah E.; Aylor, David L.; Marchuk, Douglas A. (Frontiers in Neuroscience, 2021)
Although studies with inbred strains of mice have shown that infarct size is largely determined by the extent of collateral vessel connections between arteries in the brain that enable reperfusion of the ischemic territory, we have identified strain pairs that do not vary in this vascular phenotype, but which nonetheless exhibit large differences in infarct size. In this study we performed quantitative trait locus (QTL) mapping in mice from an intercross between two such strains, WSB/EiJ (WSB) and C57BL/6J (B6). This QTL mapping revealed only one neuroprotective locus on Chromosome 8 (Chr 8) that co-localizes with a neuroprotective locus we mapped previously from F2 progeny between C3H/HeJ (C3H) and B6. The allele-specific phenotypic effect on infarct volume at the genetic region identified by these two independent mappings was in the opposite direction of the parental strain phenotype; namely, the B6 allele conferred increased susceptibility to ischemic infarction. Through two reciprocal congenic mouse lines with either the C3H or B6 background at the Chr 8 locus, we verified the neuroprotective effects of this genetic region that modulates infarct volume without any effect on the collateral vasculature. Additionally, we surveyed nonsynonymous coding SNPs and performed RNA-sequencing analysis to identify potential candidate genes within the genetic interval. Through these approaches, we suggest new genes for future mechanistic studies of infarction following ischemic stroke, which may represent novel gene/protein targets for therapeutic development.